Emergence of Orientia tsutsugamushi as an important cause of Acute Encephalitis Syndrome in India - Jain, Parul; Prakash, Shantanu; Tripathi, Piyush K.; Chauhan, Archana; Gupta, Shikha; Sharma, Umesh; Jaiswal, Anil K.; Sharma, Devraj; Jain, Amita (PLOS Neglected Tropical Diseases, 2018)
Author summary Acute encephalitis syndrome (AES) is a dreaded disease in India including the state of Bihar. Every year several people specially children, succumb to this disease and often the survivors are left with permanent residual disorders. The present research throws light on specific etiological agents that may cause AES and have found scrub typhus to be an important etiology. Knowing the specific etiology would help in definitive management of the patients that may improve the outcome both in terms of morbidity and mortality, as well as help the policy makers to take specific action for prevention and control of the disease.